Urolithiasis risk: a comparison between healthcare providers and the general population. Issue 1 (December 2016) - Chen, Ming-Hung; Weng, Shih-Feng; Hsu, Chien-Chin; Lin, Hung-Jung; Su, Shih-Bin; Wang, Jhi-Joung; Guo, How-Ran; Huang, Chien-Cheng
Abstract Background Healthcare providers have many health-related risk factors that might contribute to urolithiasis: a heavy workload, a stressful workplace, and an unhealthy quality of life. However, the urolithiasis risk in healthcare providers is not clear. Methods Using Taiwan's National Health Insurance Research Database, we identified 50, 226 physicians, 20, 677 pharmacists, 122, 357 nurses, and 25, 059 other healthcare providers as the study cohort and then randomly selected an identical number of patients who are not healthcare providers (general population) as the comparison cohort for this study. Conditional logistical regression analysis was used to compare the urolithiasis risk between healthcare providers and comparisons. Physician specialty subgroups were also analyzed. Results Physicians had a lower urolithiasis risk than did the general population (adjusted odds ratio [AOR]: 0.682; 95 % confidence interval [CI]: 0.634–0.732) and other healthcare providers (AOR: 0.661; 95 % CI 0.588–0.742) after adjusting for hypertension, diabetes, hyperlipidemia, coronary artery disease, and residence location. For pharmacists, nurses, and other healthcare providers, the urolithiasis risk was not significantly different than that for general population. Subgroup analysis showed that surgeons and family medicine physicians had a lower urolithiasis risk than did physician comparisons (AOR: 0.778; 95 % CI: 0.630–0.962 and AOR: 0.737; 95 % CI: 0.564–0.962, respectively). Conclusions Although job stress and heavy workloads affect physicians' health, physicians had a lower urolithiasis risk than did the general population and other healthcare providers. This might be attributable to their greater medical knowledge and access to healthcare. Our findings provide useful information for public health policy makers about the disease risks of healthcare providers.